The contributions of lightning to biomass turnover, gap formation and plant mortality in a tropical forest. Issue 12 (20th October 2021) - Gora, Evan M.; Bitzer, Phillip M.; Burchfield, Jeffrey C.; Gutierrez, Cesar; Yanoviak, Stephen P.
Abstract: Lightning is a common source of disturbance, but its ecological effects in tropical forests are largely undescribed. Here we quantify the contributions of lightning strikes to forest turnover and plant mortality in a lowland Panamanian forest using a real‐time lightning monitoring system. We examined 2, 195 lightning‐damaged trees distributed among 93 different strikes. None exhibited scars or fires. On average, each strike disturbed 451 m 2 (95% CI: 365–545 m 2 ), created a canopy gap of 304 m 2 (95% CI 198–454 m 2 ), and caused 7.36 Mg of woody biomass turnover (CI: 5.36–9.65 Mg). Cumulatively, we estimate that lightning strikes in this forest create canopy gaps equaling 0.39% of forest canopy area, representing 20.1% of annual gap area formation, and are responsible for 16.1% of total woody biomass turnover. Trees, lianas, herbaceous climbers and epiphytes were killed by lightning at rates 8–29 times greater than their baseline mortality rates in undamaged control sites. The likelihood of lightning‐caused death was higher for trees, lianas, and herbaceous climbers than for epiphytes, and high liana mortality suggests that lightning is an important driver of liana turnover. These results indicate that lightning influences gap dynamics, plant community composition and carbon storage capacity in some tropical forests.